Arvio t&k-verokannusteen vaikutuksista yritysten toimintaan Suomessa; A Study on the Finnish R&D Tax Credit of the Years 2013–2014 - Tero Kuusi; Mika Pajarinen; Petri Rouvinen; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2016)
– In this report, we analyze the Finnish R&D tax incentive scheme of the years 2013 and 2014. Under the scheme, firms were eligible for double corporate tax deduction incentive on labor expenses incurred for undertaking R&D activities. Our report consists of a literature review, an empirical analysis of the Finnish register data, and an internet survey. We find that the scheme failed to reach its anticipated impact. The deduction was claimed far less than expected, the actual tax loss being only 8 % of the expected tax loss. Furthermore, our analysis suggests that the R&D tax incentive failed to reach clear, blind spots in the current Finnish, mainly direct-subsidy-based innovation system. Although the scheme's design does not allow an unambiguous analysis of its impact on the R&D expenditure, our tentative results suggests that its impact remained rather small. The previous, international literature shows that the R&D tax incentives have an increasing effect on the R&D expenditures, but the impact tends not to exceed the amount of the tax subsidy. Based on our results it is unlikely that even a better-designed R&D tax deduction scheme would bring great value-added to the current, Finnish innovation system.
Keywords: O38; H25; 330; R&D; Tax credits; Forschungsfinanzierung; Steuervergünstigung; Wirkungsanalyse; Finnland